Flow Culture of Scenedesmus Dimorphus in Filtered Sago Effluent - Nur Jannah, Monib (Universiti Malaysia Sarawak, UNIMAS, 2010)
In this study, Scenedesmus dimorphus, photosynthetic green algae was cultivated in filtered sago effluent that added with NaHCO3 and compared with the filtered sago effluent without NaHCO3 to investigate the effect of the NaHCO3 to the cultivation of Scenedesmus dimorphus. The cultivation was done for 20 days in the flow culture with the speed flow 12.3 ml/sec under natural light. After the cultivation, the lipid extraction was done to determine the lipid content of Scenedesmus dimorphus. The result showed that the cultivation in FSE without NaHCO3 produced the highest dry cell weight which is 395 mg/L on day 10 of cultivation. The cultivation in FSE contain 4g/L produced 315 mg/L. There are another factor that can affect the cultivation of Scenedsmus dimorphus in FSE such as pH of medium, light and agitation. In addition, the highest lipid content of Scenedesmus dimorphus that was obtained in this study is 18.39%. Cultivation of Scenedsmus dimorphus in filtered sago effluent can be improved by providing optimum conditions such as nutrients, light, agitation and environment condition for the cultivation of this alga.